1991
DOI: 10.1073/pnas.88.13.5572
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of macromolecules into living cells: a method that exploits folate receptor endocytosis.

Abstract: Difficulties with the nondestructive delivery of macromolecules into living cells have limited the potential applications of antibodies, genes, enzymes, peptides, and antisense oligonucleotides in biology and medicine. We have found, however, that the natural endocytosis pathway for the vitamin folate can be exploited to nondestructively introduce macromolecules into cultured cells if the macromolecule is first covalently linked to folate. Thus, treatment of KB cells with folate-conjugated ribonuclease, horser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
338
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(354 citation statements)
references
References 42 publications
12
338
0
1
Order By: Relevance
“…2), for hFRα or hFRβ via isothermal titration calorimetry at pH 7.4 and pH 6.5. A general expectation given the proposed pH dependence model for ligand release is that a lower affinity for folate would be seen at pH 6.5, the average pH of the recycling endosome (Table 1; Table S3) (2,42,53,63). Isothermal titration calorimetry (ITC) measurements demonstrate that hFRα has an extremely high affinity for folate with a dissociation constant (K d ) of ∼10 pM at pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…2), for hFRα or hFRβ via isothermal titration calorimetry at pH 7.4 and pH 6.5. A general expectation given the proposed pH dependence model for ligand release is that a lower affinity for folate would be seen at pH 6.5, the average pH of the recycling endosome (Table 1; Table S3) (2,42,53,63). Isothermal titration calorimetry (ITC) measurements demonstrate that hFRα has an extremely high affinity for folate with a dissociation constant (K d ) of ∼10 pM at pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…This way there is a potential in the targeting of activated macrophages using FR-β as target. It's possible to perform this targeting conjugating folate or folic acid on the drug system surface [79,93]. Chandrasekar et al, for example, created a folate-dendrimer conjugate loaded with indomethacin for specific drug delivery to inflammatory sites.…”
Section: Active Targetingmentioning
confidence: 99%
“…The basis for FRa-targeted drug delivery lies in the substrate specificity of folic acid to FRa. In a series of experiments, Leamon et al 94 showed that covalent conjugation of folic acid with various pharmaceuticals such as horseradish peroxidase, IgG serum albumin and ribonuclease, resulted in the nondestructive intracellular delivery of these molecules via FRa. In a subsequent study, the authors showed that cellular protein synthesis was inhibited in a time and dose dependent manner by the uptake of the folic acid-toxin conjugate into the cell, providing direct evidence that folic acid conjugates not only reach the cytoplasm but do so in a functionally active form.…”
Section: Exploitation Of Fra For Therapeutic and Diagnostic Potentialmentioning
confidence: 99%